Partial cystectomy of prolapsed urinary bladder in yellow-footed tortoise (Chelonoidis denticulata) - Tardivo, Caio Eduardo Okamoto [UNESP]; Ichikawa, Ricardo Shoiti [UNESP]; Rahal, Sheila Canevese [UNESP]; da Silva, Jeana Pereira [UNESP]; Mamprim, Maria Jaqueline [UNESP] (Wiley, 2024)
An adult yellow-footed female tortoise (Chelonoidis denticulata) weighing 7.6 kg was voluntarily surrendered to the environmental police. The history-taking could not be obtained due to a lack of information. Upon physical examination, a fluid-filled structure prolapsed through the cloacal opening was observed. The aspirated fluid had a citrine-yellow colour, suggesting urinary bladder prolapse, which was successfully reduced back into the coelomic cavity with the hydrostatic reduction technique. The following day, prolapse recurrence was observed. In addition, distal two-thirds of the organ had a darkened coloration. Whole-body radiographs revealed four eggs ready for oviposition. Partial cystectomy of the prolapsed urinary bladder was done. Pretreatment with calcium followed by oxytocin was used for nonobstructive egg retention, and all eggs were laid. After 2.4 years of the surgery, the tortoise did not experience a recurrence of bladder prolapse.